Research progress of electromagnetic pulse welding technology: A review - Zilong Su; Limeng Yin; Hong Jiang; Long Zhang; Yuhua Chen; Liping Zhang; Hehe Zhang; Wei Feng (Journal of Materials Research and Technology)
The purpose is to explore the welding principle and interface bonding mechanism of electromagnetic pulse welding technology and understand the microstructure and properties of welded joints, the production and application of electromagnetic pulse welding technology in actual industry are further promoted. This paper provides a comprehensive review of this technology. The equipment and characteristics of electromagnetic pulse welding are outlined, along with its circuit device and system. The principles and parameters of electromagnetic pulse welding are discussed, including the circuit principle and combination principle. Furthermore, this study highlights the outstanding performance of the microstructure and properties of electromagnetic pulse welding, and the simulation progress of related equipment components and experimental process parameters. Finally, the future research focus and development trends are explored. It provides a reference for further promoting the wide application and rapid development of electromagnetic pulse welding technology. It provides a reference for accelerating the development of electromagnetic pulse welding technology and putting it into industrial production, extensively.